2012
DOI: 10.1093/icvts/ivs037
|View full text |Cite
|
Sign up to set email alerts
|

Is routine chest radiography indicated following chest drain removal after cardiothoracic surgery?

Abstract: A best evidence topic was written according to a structured protocol. The question addressed was whether routine chest radiography is indicated following chest drain removal in patients undergoing cardiothoracic surgery. A total of 356 papers were found using the reported searches; of which, 6 represented the best evidence to answer the clinical question. The authors, date, journal, study type, population, main outcome measures and results are tabulated. Reported measures were mean duration of drains left in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 7 publications
1
26
0
Order By: Relevance
“…A meta-analysis published in 2013 collected data from seven studies investigating the usefulness of daily CR after pulmonary operations and concluded clearly that forgoing routine CR significantly decreases costs with no effect on mortality rates, hospital length of stay, or adverse events [19]. Regarding management after drain removal, Sepehripour and colleagues [9] analysed six studies with level 3 evidence showing that routine CR after drain removal provides no diagnostic or therapeutic advantage over clinically indicated CR or simple clinical assessment. Nevertheless, most of the procedures in the populations analyzed were cardiac operations in which there should be no active air leak from lung parenchyma.…”
Section: Commentmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis published in 2013 collected data from seven studies investigating the usefulness of daily CR after pulmonary operations and concluded clearly that forgoing routine CR significantly decreases costs with no effect on mortality rates, hospital length of stay, or adverse events [19]. Regarding management after drain removal, Sepehripour and colleagues [9] analysed six studies with level 3 evidence showing that routine CR after drain removal provides no diagnostic or therapeutic advantage over clinically indicated CR or simple clinical assessment. Nevertheless, most of the procedures in the populations analyzed were cardiac operations in which there should be no active air leak from lung parenchyma.…”
Section: Commentmentioning
confidence: 99%
“…Very limited data are available on the follow-up of patients after chest tube removal, specifically after lung resections, but the general feeling is to obtain an imaging study to confirm lung expansion. The literature on this topic [9,10] is inconsistent in terms of populations and surgical procedures. However, lung ultrasound (LUS) has been well documented to be highly accurate in detecting pneumothorax (PTx) in the trauma setting has [11].…”
mentioning
confidence: 99%
“…Multiple investigators have studied the clinical value of routine CXRs after central venous catheterization, endotracheal intubation, and chest tube placement or removal. [1][2][3][4][5][6][7][8][9][10][11][12] Others have studied the value of daily routine CXRs in a mixed ICU population, or in mechanically ventilated patients only. [13][14][15][16][17][18][19][20][21] The diagnostic and therapeutic efficacy of all these routine CXRs has been reported to be low.…”
Section: See Editorial Commentary Page 230mentioning
confidence: 99%
“…Chest radiographs (CXRs) are obtained frequently for intensive care unit (ICU) patients, on a routine basis, after a change in clinical situation or after surgery and other certain procedures. Multiple investigators have studied the clinical value of routine CXRs following central venous catheterization, endotracheal intubation and chest tube placement or removal [ 1 ]-[ 12 ]. Others have studied the value of daily routine CXRs in a mixed ICU population or in mechanically ventilated patients only [ 13 ]-[ 22 ] The diagnostic and therapeutic efficacy of these routine CXRs is known to be low [ 1 ]-[ 3 ],[ 6 ]-[ 9 ],[ 11 ],[ 13 ],[ 14 ],[ 16 ]-[ 19 ],[ 22 ].…”
Section: Introductionmentioning
confidence: 99%